Clinical and molecular findings in 39 patients with KBG syndrome caused by deletion or mutation of ANKRD11. Issue 11 (8th September 2016) - Goldenberg, Alice; Riccardi, Florence; Tessier, Aude; Pfundt, Rolph; Busa, Tiffany; Cacciagli, Pierre; Capri, Yline; Coutton, Charles; Delahaye‐Duriez, Andree; Frebourg, Thierry; Gatinois, Vincent; Guerrot, Anne‐Marie; et al.
Abstract : KBG syndrome, due to ANKRD11 alteration is characterized by developmental delay, short stature, dysmorphic facial features, and skeletal anomalies. We report a clinical and molecular study of 39 patients affected by KBG syndrome. Among them, 19 were diagnosed after the detection of a 16q24.3 deletion encompassing the ANKRD11 gene by array CGH. In the 20 remaining patients, the clinical suspicion was confirmed by the identification of an ANKRD11 mutation by direct sequencing. We present arguments to modulate the previously reported diagnostic criteria. Macrodontia should no longer be considered a mandatory feature. KBG syndrome is compatible with autonomous life in adulthood. Autism is less frequent than previously reported. We also describe new clinical findings with a potential impact on the follow‐up of patients, such as precocious puberty and a case of malignancy. Most deletions remove the 5'end or the entire coding region but never extend toward 16q telomere suggesting that distal 16q deletion could be lethal. Although ANKRD11 appears to be a major gene associated with intellectual disability, KBG syndrome remains under‐diagnosed. NGS‐based approaches for sequencing will improve the detection of point mutations in this gene. Broad knowledge of the clinical phenotype is essential for a correct interpretation of the molecular results. © 2016 Wiley Periodicals, Inc.